BVOC Emissions From a Subarctic Ecosystem, as Controlled by Insect Herbivore Pressure and Temperature - Ghimire, Rajendra P.; Silfver, Tarja; Myller, Kristiina; Oksanen, Elina; Holopainen, Jarmo K.; Mikola, Juha (Ecosystems, 2021)
Abstract The biogenic volatile organic compounds, BVOCs have a central role in ecosystem–atmosphere interactions. High-latitude ecosystems are facing increasing temperatures and insect herbivore pressure, which may affect their BVOC emission rates, but evidence and predictions of changes remain scattered. We studied the long-term effects of + 3 °C warming and reduced insect herbivory (achieved through insecticide sprayings) on mid- and late summer BVOC emissions from field layer vegetation, supplemented with birch saplings, and the underlying soil in Subarctic mountain birch forest in Finland in 2017–2018. Reduced insect herbivory decreased leaf damage by 58–67% and total ecosystem BVOC emissions by 44–72%. Of the BVOC groups, total sesquiterpenes had 70–80% lower emissions with reduced herbivory, and in 2017 the decrease was greater in warmed plots (89% decrease) than in ambient plots (34% decrease). While non-standardized total BVOC, monoterpene, sesquiterpene and GLV emissions showed instant positive responses to increasing chamber air temperature in midsummer samplings, the long-term warming treatment effects on standardized emissions mainly appeared as changes in the compound structure of BVOC blends and varied with compounds and sampling times. Our results suggest that the effects of climate warming on the total quantity of BVOC emissions will in Subarctic ecosystems be, over and above the instant temperature effects, mediated through changes in insect herbivore pressure rather than plant growth. If insect herbivore numbers will increase as predicted under climate warming, our results forecast herbivory-induced increases in the quantity of Subarctic BVOC emissions. Graphic Abstract